Seronegative Autoimmune Encephalomyelitis with Area Postrema Symptoms - David Andrew Prentice; Ravi Ambati; Lay K. Kho; Thomas Jenkins; Paul M. Parizel (Case Reports in Neurology)
Introduction: Patients presenting with encephalopathy and longitudinally extensive myelitis pose a significant diagnostic challenge. Area postrema-related symptoms, such as intractable hiccoughs, can aid in narrowing the differential diagnosis. Neuromyelitis optica spectrum disorders and glial fibrillary acidic protein (GFAP) autoimmune encephalitis are known causes; however, some cases remain seronegative, suggesting the presence of unidentified autoantibodies or immune targets. Case Presentation: A previously healthy man in his 70s presented with headache, fever, and confusion, followed by a seizure and persistent hiccoughs. MRI revealed brainstem involvement and extensive transverse myelitis. Cerebrospinal fluid (CSF) analysis showed inflammatory features, but testing for AQP4, MOG, and GFAP antibodies was initially negative. He was treated with intravenous corticosteroids and plasma exchange, after which serum GFAP-IgG was weakly positive, though CSF remained negative. His condition improved with immunotherapy, but significant lower limb weakness persisted. Based on clinical and radiological findings, we hypothesize that tanycytes – specialized glial cells in the area postrema – may be an additional immune target in GFAP encephalitis. Conclusion: This case highlights a seronegative encephalomyelitis syndrome with area postrema involvement, possibly implicating glial cells beyond astrocytes. Further studies are needed to explore the role of tanycytes in autoimmune neuroinflammation.